Praefationes minores: prologi wewnętrzne w Ab urbe condita Liwiusza = Praefationes minores: internal prologues in Livy's Ab urbe condita - Pigoń, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Apart from the famous praefatio (maior), Livy's introduction to the Ab Urbe Condita as a whole, there are in the extant parts of this work four internal prologues (or praefationes minores), marking the beginnings of, respectively, books 2, 6, 21 and 31. In the present paper a short overview of prologues, and especially internal prologues, in ancient historiography is followed by a more detailed discussion of the four Livian passages.
Keywords: Titus Livius (59 p.n.e.- 17 n.e.); historiografia antyczna; prologi dzieł historycznych; wypowiedzi programowe historyków; ancient historiography; historical prologues; historical writers' programmatic statements